2018
DOI: 10.7150/ijbs.25629
|View full text |Cite
|
Sign up to set email alerts
|

Cellular glucose metabolism is essential for the reduction of cell-impermeable water-soluble tetrazolium (WST) dyes

Abstract: Water-soluble tetrazolium (WST) dyes, such as WST-1 and WST-8, are widely used in cell proliferation and anti-cell-growth drug screen assays. However, the underlying determinants for WST reduction are still largely unknown. In addition, application of tetrazolium-based assays to cellular glucose metabolism studies has not been fully explored. In the present study, we show here that WST-8 reduction is dependent on cellular glucose metabolism. In order to minimize the variance of live cell number during stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The washed cells were then treated with 50 μL of dimethyl sulfoxide (DMSO) and mixed to solubilize the formazan crystals formed by living cells. 32 Absorbance was measured at 570 nm in a microplate reader (TECAN spark cyto, Switzerland). The cell viability (%) was calculated in percentage according to the following equation …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The washed cells were then treated with 50 μL of dimethyl sulfoxide (DMSO) and mixed to solubilize the formazan crystals formed by living cells. 32 Absorbance was measured at 570 nm in a microplate reader (TECAN spark cyto, Switzerland). The cell viability (%) was calculated in percentage according to the following equation …”
Section: Methodsmentioning
confidence: 99%
“…The HIEC-6 cells were seeded (5 × 10 4 cells/well) in a 96 well plate; after reaching 70–80% confluency, cells were fed with different concentrations of extracts (12.5, 25, 50, and 100 ppm) to a final volume of 100 μL and incubated for 24 h. After 24 h of incubation, the cells were rinsed with 1× PBS; then, 100 μL of MTT solution was added and incubated for 4 h at 37 °C in a CO 2 incubator (New Brunswick, Galaxy 170R, Eppendorf Company). The washed cells were then treated with 50 μL of dimethyl sulfoxide (DMSO) and mixed to solubilize the formazan crystals formed by living cells . Absorbance was measured at 570 nm in a microplate reader (TECAN spark cyto, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…The WST‐8 cell proliferation test we used was based on intracellular dehydrogenase activity. Generally, this method compares the number of cells with an indicated amount of dehydrogenase activity in each sample, but it also depends on the metabolic status of the cells [ 31 ]. Therefore, the number of viable cells was examined using Hoechst 33342, 48 h after the administration of 25 μ m TAT.…”
Section: Resultsmentioning
confidence: 99%
“…the metabolic status of the cells [31]. Therefore, the number of viable cells was examined using Hoechst 33342, 48 h after the administration of 25 M of TAT.…”
Section: Accepted Articlementioning
confidence: 99%
“…Irrespective of GM-CSF activation, the metabolic activity of ex vivo cultivated monocytes was generally increased after both static and dynamic culture conditions compared to freshly isolated monocytes. According to results from tumor cell lines, an increased reduction of the tetrazolium salt WST1 was associated with increased glucose metabolism [ 19 ], indicating an increased energy demand of monocytes during suspension culture. Further studies revealed that increased glycolysis was associated with the rapid production of various metabolites that support cellular activities and cell growth [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%